2023
DOI: 10.5312/wjo.v14.i3.90
|View full text |Cite
|
Sign up to set email alerts
|

Utility of D-dimer in total joint arthroplasty

Abstract: As the number of patients receiving total joint replacements continues to rise, considerable attention has been directed towards the early detection and prevention of postoperative complications. While D-dimer has long been studied as a diagnostic tool in venous thromboembolism (VTE), this assay has recently received considerable attention in the diagnosis of periprosthetic joint infection (PJI). D-dimer values are substantially elevated in the acute postoperative period after total joint arthroplasty, with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…However, it is important to exercise caution when interpreting D-dimer levels in patients with inflammatory and hypercoagulable disorders as diagnostic thresholds may be higher in this patient population [ 56 ].…”
Section: Diagnostic Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to exercise caution when interpreting D-dimer levels in patients with inflammatory and hypercoagulable disorders as diagnostic thresholds may be higher in this patient population [ 56 ].…”
Section: Diagnostic Testsmentioning
confidence: 99%
“…Furthermore, they found that D-dimer demonstrated the highest sensitivity for PJI caused by indolent organisms at 94%. However, it is important to exercise caution when interpreting D-dimer levels in patients with inflammatory and hypercoagulable disorders as diagnostic thresholds may be higher in this patient population [56].…”
Section: D-dimermentioning
confidence: 99%
“…72 The role of D-dimer in the diagnosis of peri-prosthetic infections merits special mention. 73,74 A systematic review and meta-analysis based on 12 studies including a total of 1,818 patients concluded that D-dimer has sufficient diagnostic accuracy to exclude peri-prosthetic joint infection. 75 In addition, the updated 2018 Musculoskeletal Infection Society criteria validated a score for the diagnosis of peri-prosthetic hip and knee infections which included D-dimer levels >860 µg/L.…”
Section: Cancer Inflammation and Infectionmentioning
confidence: 99%